Predictability of Chile El Niño: insights from a low-order modeling approach - Eduardo Martínez; Cristian Martinez-Villalobos; Boris Dewitte (Climate Dynamics, 2026)

Population genomic analysis of Petrolisthes violaceus (Anomura:Porcellanidae) reveals two genetic groups along the Southeast Pacific coast (20.4°S–41.8°S) - Juan Soto; Noemí Rojas-Hernandez; Boris Dewitte; Catalina Llancaleo-Araya; Caren Vega-Retter; Luis Miguel Pardo; Carolina Parada; David Véliz (Regional Studies in Marine Science, 2026)

Evaluation of temperature on survival, metabolism, and morphological changes in Palm ruff (Seriolella violacea) larvae - Begoña Cárcamo; Boris Dewitte; Alexandra Parouffe; Aurélien Paulmier; Véronique Garçon; Laura Ramajo; Sebastián San Martín; Juan Varas; Marcia Oliva; Edison Serrano; Nieves Sandoval; Katherine Jeno; et al. (Aquaculture, 2026)

Perceptions of oyster farmers on adopting environmental monitoring technologies to mitigate ocean acidification: A case study in Bahía San Quintín, México - Guadalupe Gómez-Hernández; Orion Norzagaray-López; José Martín Hernández-Ayón; Véronique Garçon; Boris Dewitte; Gabriela Yareli Cervantes-Díaz (Ocean & Coastal Management, 2026)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Chile Niño/Niña in the coupled model intercomparison project phases 5 and 6 - Emilio Concha; Boris Dewitte; Cristian Martinez-Villalobos; Fabien Solmon; Emilia Sanchez-Gomez (Climate Dynamics, 2024)
The north and central coast of Chile is influenced by El Niño-Southern Oscillation (ENSO) through oceanic and atmospheric teleconnections. However, it also experiences episodic oceanic warmings off central Chile (30°S) lasting a few months that are not necessarily associated with ENSO. These episodes, called “Chile Niño” events, besides their ecological and socio-economical impacts, have also the potential to influence tropical Pacific variability. Here, we investigate how realistically the models in the Coupled Model Intercomparison Project (CMIP, Phases 5 and 6) simulate Chile Niño/Niña (CN) events, and quantify their changes under anthropogenic forcing. Despite limitations of the global models in simulating realistically coastal upwelling dynamics, we show that they simulate reasonably well the observed spatial pattern, amplitude and seasonal evolution of CN events. They however fail to properly represent the positive skewness from observations. The analysis of a sub-group of models (36) that simulate ENSO realistically reveals that CN events increase in amplitude and variance in the future climate with no changes in their frequency of occurence. This is interpreted as resulting from compensating effects amongst changes in remote drivers and local feedbacks. In particular, ENSO variance increases while that of the South Pacific Oscillation decreases. Conversely, we found that while the Wind-Evaporation-SST feedback tends to increase and the coupling between mixed-layer depth and SST weakens, favoring the development of CN events, the thermocline and wind-SST feedbacks decrease. However, only the change in the thermocline feedback is correlated to changes in CN variance amongst the models, suggesting a dominant role of local oceanic stratification changes in constraining the sensitivity of CN to global warming.

On the role of onshore geostrophic flow on larval retention in a permanent upwelling zone along north-central Chile - Eduardo A. Flores; Marcel Ramos; Boris Dewitte; Orlando Astudillo; Lucas Glasner (Frontiers in Marine Science, 2024)
The Humboldt Archipelago (HAp), located off north-central Chile (~28° - 33° S) is one of the most productive marine zones of the Humboldt Current System (HCS). This area lies within a permanent upwelling zone, characterized by two upwelling centers, 100 km apart, that define the Coquimbo Bays System (CBS). The resulting increase in primary productivity and larval retention are mentioned as the main factors that explain the high biodiversity. However, how these upwelling centers interact remains unclear due to the interplay of various physical features such as the general circulation, the meso- and submeso-scale structures (e.g., eddies), and remote and local forcings (e.g., winds, topography) that affect larval transport in the HAp. In this study, we focus on the role played by geostrophic and Ekman currents in controlling the retention (and dispersion) of particles in these centers based on the analyses of satellite data and hydrodynamic model outputs. Lagrangian models are in particular carried out to document particles’ transport during selected oceanic conditions corresponding to whether Ekman transport or geostrophic recirculation prevails or are debilitated. The latitudinal variation of the Ekman transport reveals two maxima at each upwelling center with differences in spatial extent but not in intensity. Mean zonal geostrophic current occurs in alternating flow at each upwelling center. Results of the Lagrangian experiments highlight the importance of the cross-shore geostrophic flow on larval transport, where an increased transport of particles to the north and northwest occurs at the southern upwelling center, while the northern upwelling center (where HAp is located) received particles from the south and retained particles released in the same area, which is related to the cyclonic geostrophic recirculation and lower Ekman transport. Particle retention increased with depth and under the relaxation and downwelling scenarios revealing the importance of wind alternation for larval retention. The CBS could act as an upwelling shadow in the south and an upwelling trap in the north where the onshore flow of geostrophic current could enhance larval retention and recruitment over longer periods when compared with the Ekman transport timescale.

Abundance and diversity of diatoms and dinoflagellates in an embayment off Central Chile (30°S): evidence of an optimal environmental window driven by low and high frequency winds - Barbara Gianella Jacob; Orlando Astudillo; Boris Dewitte; María Valladares; Gonzalo Alvarez Vergara; Carolina Medel; David W. Crawford; Eduardo Uribe; Beatriz Yanicelli (Frontiers in Marine Science, 2024)
The relationship between phytoplankton abundances and wind forcing in upwelling systems involves a number of processes that make the relationship nonlinear in nature. In particular, although upwelling-favorable winds tend to provide nutrients for phytoplankton growth, they can also induce export of both biomass and nutrients to the open ocean through Ekman and eddy-induced transport, or dilution of populations through vertical mixing, which negatively impacts increase in biomass. These processes are essentially nonlinear and can interact antagonistically or synergistically on the overall coastal accumulation of biomass. Consequently, producers and consumers tend to decline above a certain wind threshold despite input of nutrient-enriched water. We have observed this phenomenon in an embayment off Central Chile (30°S), where almost 10 years (2000-2009) of microphytoplankton data were analyzed together with environmental variables and wind phenology. Our findings showed that abundance, species diversity and evenness of diatoms and dinoflagellates all increased post-2005 when the mean of the alongshore surface wind stress reached a maximum threshold value of 0.026 N m -2 , observed at the decadal temporal variability scale. The increased abundances of diatoms and dinoflagellates post-2005 was associated with the changing phase of the Pacific Decadal Oscillation (PDO) from positive (warm) to negative (cold) phases, which was also associated with a decrease in the intra-seasonal wind activity. Both abundance and diversity of the microphytoplankton community peaked during the post-2005 period whereas higher abundances and frequency of harmful algal blooms (e.g. Pseudo-nitzschia australis ) were observed prior to 2005. We suggest that the low-frequency (decadal) variations of mean wind stress during a transition phase of the PDO combined with the reduction in intra-seasonal (periods shorter than 2 months) wind variability after 2005 provided an “optimal environmental window” for the ecosystem.

Revisiting historical trends in the Eastern Boundary Upwelling Systems with a machine learning method - David F. Bustos; Diego A. Narváez; Boris Dewitte; Vera Oerder; Mabel Vidal; Fabián Tapia (Frontiers in Marine Science, 2024)
Eastern boundary upwelling systems (EBUS) host very productive marine ecosystems that provide services to many surrounding countries. The impact of global warming on their functioning is debated due to limited long-term observations, climate model uncertainties, and significant natural variability. This study utilizes the usefulness of a machine learning technique to document long-term variability in upwelling systems from 1993 to 2019, focusing on high-frequency synoptic upwelling events. Because the latter are modulated by the general atmospheric and oceanic circulation, it is hypothesized that changes in their statistics can reflect fluctuations and provide insights into the long-term variability of EBUS. A two-step approach using Self-Organizing Maps (SOM) and Hierarchical Agglomerative Clustering (HAC) algorithms was employed. These algorithms were applied to sets of upwelling events to characterize signatures in sea-level pressure, meridional wind, shortwave radiation, sea-surface temperature (SST), and Ekman pumping based on dominant spatial patterns. Results indicated that the dominant spatial pattern, accounting for 56%-75% of total variance, representing the seasonal pattern, due to the marked seasonality in along-shore wind activity. Findings showed that, except for the Canary-Iberian region, upwelling events have become longer in spring and more intense in summer. Southern Hemisphere systems (Humboldt and Benguela) had a higher occurrence of upwelling events in summer (up to 0.022 Events/km²) compared to spring (<0.016 Events/km²), contrasting with Northern Hemisphere systems (<0.012 Events/km²). Furthermore, long-term changes in dominant spatial patterns were examined by dividing the time period in approximately two equally periods, to compare past changes (1993-2006) with relatively new changes (2007-2019), revealing shifts in key variables. These included poleward shifts in subtropical high-pressure systems (SHPS), increased upwelling-favorable winds, and SST drops towards higher latitudes. The Humboldt Current System (HumCS) exhibited a distinctive spring-to-summer pattern, with mid-latitude meridional wind weakening and concurrent SST decreases. Finally, a comparison of upwelling centers within EBUS, focusing on changes in pressure and temperature gradients, meridional wind, mixed-layer depth, zonal Ekman transport, and Ekman pumping, found no evidence supporting Bakun’s hypothesis. Temporal changes in these metrics varied within and across EBUS, suggesting differential impacts and responses in different locations.

Population genomic and biophysical modeling show different patterns of population connectivity in the spiny lobster Jasus frontalis inhabiting oceanic islands - Felipe Rojas-Araos; Noemi Rojas-Hernández; Sebastián Cornejo-Guzmán; Billy Ernst; Boris Dewitte; Carolina Parada; David Veliz (Marine Environmental Research, 2024)

Oxidative conditions along the continental shelf of the Southeast Pacific during the last two millennia: a multiproxy interpretation of the oxygen minimum zone variability from sedimentary records - Praxedes Muñoz; Alexis Castillo; Jorge Valdés; Boris Dewitte (Frontiers in Marine Science, 2023)
The oxygen minimum zone (OMZ) is an essential feature along the Pacific margin, extensively studied for its influence on benthic fauna, acquiring relevance in coastal zones due to its impact on aquaculture species, marine-managed areas, and marine-protected areas. The most evident temporal variability beyond seasonal timescales observed for the OMZ was related to inter-annual variability associated with El Niño, when warmer and more oxygenated waters arrive at shallower zones and the OMZ becomes deeper. However, the impact of oxygen-deficient water that appears sporadically over the shelf is not yet understood. This study provides an integrated view of the oceanographic and climatic conditions behind bottom oxygen conditions along the Chilean continental margin, considering the temporal variability in the South East (SE) Pacific during the last ~2000 years. We organized the information on redox-sensitive metals and δ 15 N from sedimentary cores obtained from shelf zones from 23°S to 36°S at water depths lower than 100 m. The results demonstrate the variability in the upper part of the OMZ over the shelf, which seems to respond to climatic oscillations. The element distribution indicated in particular a more intense OMZ was developed over the shelf before 1400 AD, followed by more oxygenated bottom conditions afterward, except between 1925 and 1970 off 36°S when the OMZ was intensified, a condition that was not observed at the northern sites. This period mostly coincided with a low Pacific Decadal Oscillation amplitude and reduced El Niño Southern Oscillation (ENSO) activity. In the last 50 years, the proxy data suggests less intense suboxic environment along the Chilean margin. This weakening of the upper boundary of the OMZ in the last decades is interpreted as resulting from the accumulative effect of ventilation processes at different time scales.

On the interpretation of changes in the subtropical oxygen minimum zone volume off Chile during two La Niña events (2001 and 2007) - Matías Pizarro-Koch; Oscar Pizarro; Boris Dewitte; Ivonne Montes; Aurélien Paulmier; Véronique Garçon; Hector Hito Sepulveda; Andrea Corredor-Acosta; Catalina Aguirre; Marcel Ramos (Frontiers in Marine Science, 2023)
Oxygen minimum zones (OMZs) are extended oceanic regions for which dissolved oxygen concentration is extremely low. They are suspected to be expanding in response to global warming. However, currently, the mechanisms by which OMZ varies in response to climate variability are still uncertain. Here, the variability of the subtropical OMZ off central Chile of a regional coupled physical–biogeochemical regional model simulation was analyzed for the period 2000–2008, noting that its fluctuations were significant despite the relatively weak amplitude of the El Niño/Southern Oscillation (ENSO). In particular, the interannual variability in the OMZ volume (OMZ VOL , defined as the volume with dissolved oxygen concentration (DO) ≤ 45μM) was approximately 38% larger than that of the seasonal cycle, with maximum and minimum anomalies of OMZ VOL taking place during two cold La Niña (LN) years (2001 and 2007). The model analyses further reveal that these anomalies resulted from a combined effect of changes in (1) the oxygen-poor waters poleward transport by the Peru–Chile undercurrent (PCUC), (2) the intensity of quasi-zonal jets influencing the transport of water to and from the OMZ, and (3) the zonal DO transport related to mesoscale eddy activity. Specifically, the interannual variability of the PCUC modulated primarily the DO contents of the OMZ core [(DO) ≤ 20μM] and secondarily the OMZ VOL , while cross-shore DO transport by the zonal jets and the eddy fluxes played a major role in ventilating and shaping the offshore extent of the OMZ. When the OMZ VOL was maximum (minimum), the PCUC transport was slightly increased (reduced), which was associated with a reduction (increase) in the ventilation of the OMZ through negative (positive) anomalies of zonal advection and DO eddy fluxes. Our results demonstrate that significant natural interannual variability in the subtropical OMZ off Chile originates from the interplay between oceanic equatorial teleconnection (PCUC transport) and local non-linear dynamics (the zonal jets and mesoscale eddies).

Evaluating future climate change exposure of marine habitat in the South East Pacific based on metabolic constraints - Alexandra Parouffe; Véronique Garçon; Boris Dewitte; Aurélien Paulmier; Ivonne Montes; Carolina Parada; Ariadna Mecho; David Veliz (Frontiers in Marine Science, 2023)
Introduction On-going climate change is now recognized to yield physiological stresses on marine species, with potentially detrimental effects on ecosystems. Here, we evaluate the prospect of using climate velocities (CV) of the metabolic index (Φ) for assessing changes in habitat in the South East Pacific. Methods Our approach is based on a species with mean ecophysiotype (i.e. model species) and the use of a global Earth System Model simulation (CESM-LE) under RCP 8.5 scenario. The SEP is chosen as a case study as it hosts an Oxygen Minimum Zone and seamounts systems sustaining local communities through artisanal fisheries. Results and Discussion Our results indicate that CV Φ pattern is mainly constrained by the oxygen distribution and that its sign is affected by contrasting oxygen trends (including a re-oxygenation in the upper OMZ) and warming. We further show that CV Φ is weakly dependent on physiological traits composing Φ, which conveys to this metrics some value for inferring the projected mean displacement and potential changes in viability of metabolic habitat in a region where physiological data are scarce. Based on sensitivity experiments to physiological traits and natural variability, we propose a general method for inferring broad areas of climate change exposure regardless of species-specific Φ. We show in particular that for the model used here, the upper OMZ region can be considered a “safe” area for the species with ecophysiotype close to that of 71 species used to derive the model species. Limitations of the approach and perspectives of this work are also discussed.

Spatial and seasonal variability of horizontal temperature fronts in the Mozambique Channel for both epipelagic and mesopelagic realms - Floriane Sudre; Boris Dewitte; Camille Mazoyer; Véronique Garçon; Joel Sudre; Pierrick Penven; Vincent Rossi (Frontiers in Marine Science, 2023)
Introduction Ocean fronts are moving ephemeral biological hotspots forming at the interface of cooler and warmer waters. In the open ocean, this is where marine organisms, ranging from plankton to mesopelagic fish up to megafauna, gather and where most fishing activities concentrate. Fronts are critical ecosystems so that understanding their spatio-temporal variability is essential not only for conservation goals but also to ensure sustainable fisheries. The Mozambique Channel (MC) is an ideal laboratory to study ocean front variability due to its energetic flow at sub-to-mesoscales, its high biodiversity and the currently debated conservation initiatives. Meanwhile, fronts detection relying solely on remotely-sensed Sea Surface Temperature (SST) cannot access aspects of the subsurface frontal activity that may be relevant for understanding ecosystem dynamics. Method In this study, we used the Belkin and O’Reilly Algorithm on remotely-sensed SST and hindcasts of a high-resolution nested ocean model to investigate the spatial and seasonal variability of temperature fronts at different depths in the MC. Results We find that the seasonally varying spatial patterns of frontal activity can be interpreted as resulting from main features of the mean circulation in the MC region. In particular, horizontally, temperature fronts are intense and frequent along continental shelves, in islands’ wakes, at the edge of eddies, and in the pathways of both North-East Madagascar Current (NEMC) and South-East Madagascar Current (SEMC). In austral summer, thermal fronts in the MC are mainly associated with the Angoche upwelling and seasonal variability of the Mozambique current. In austral winter, thermal fronts in the MC are more intense when the NEMC and the Seychelles-Chagos and South Madagascar upwelling cells intensify. Vertically, the intensity of temperature fronts peaks in the vicinity of the mean thermocline. Discussion Considering the marked seasonality of frontal activity evidenced here and the dynamical connections of the MC circulation with equatorial variability, our study calls for addressing longer timescales of variability to investigate how ocean ecosystem/front interactions will evolve with climate change.

On the Relationship Between Tropical Instability Waves and Intraseasonal Equatorial Kelvin Waves in the Pacific From Satellite Observations (1993–2018) - M. Gabriela Escobar-Franco; Julien Boucharel; Boris Dewitte (Frontiers in Marine Science, 2022)
Intraseasonal Kelvin waves (IKWs) and Tropical Instability Waves (TIWs) are essential components of the tropical Pacific coupled climate variability. While downwelling IKWs are precursors of ENSO (e.g., the El Niño Southern Oscillation), TIWs contribute to its asymmetry by mixing more/less warm off-equatorial and cold tongue waters during La Niña/El Niño. Theoretical studies and a few observational case studies also suggest that TIWs and IKWs can interact non-linearly. However, owing to the chaotic nature of TIWs, observational evidence that such a process occurs consistently has not been established thus far. Here, we document for the first time their interaction from satellite observations over a period spanning almost 30 years (1993–2018). From complex empirical orthogonal functions analysis and sea level decomposition into meridional modes, we evidence that a substantial share (∼42%) of the variance of TIWs-induced intraseasonal sea level anomalies are associated with IKWs activity. We show that non-linear dynamical heating (NDH) in the Eastern equatorial Pacific associated with this intraseasonal mode can be as large as that for interannual time scales. Implications for understanding the eastern tropical Pacific heat budget and ENSO variability are discussed.

On the relationship between ENSO diversity and the ENSO atmospheric teleconnection to high‐latitudes - Daria Gushchina; Maria Kolennikova; Boris Dewitte; Sang‐Wook Yeh (International Journal of Climatology, 2022)
The El Niño‐Southern Oscillation (ENSO) has experienced changes in its properties since the 1990s, particularly increased occurrence of Central Pacific El Niño events. These events have influenced atmospheric circulation in the mid to high‐latitudes of both hemispheres through atmospheric teleconnection. Here it is shown that, in the Northern Hemisphere, the planetary circulation response to the Eastern Pacific (EP) event in boreal winter is associated with Rossby waves propagating poleward and is mostly confined to the Pacific region, while the Central Pacific (CP) event induces a negative phase of Arctic Oscillation (AO)‐like circulation pattern at planetary scale. In the Southern Hemisphere (SH), the difference between the circulation patterns associated with the two types of El Niño in austral summer is rather small and the response of the tropospheric circulation consists of an Antarctic Oscillation (AAO)‐like negative phase pattern. In the SH, the circulation response to CP Niño lasts longer than that to EP Niño. In particular, during EP Niño the composite circulation anomalies reverse sign from austral summer to winter, which is not the case during CP event. This adds an interhemispheric asymmetry dimension to the ENSO atmospheric teleconnection in the high‐latitudes in relation to ENSO diversity. These changes in the circulation are associated with surface air‐temperature anomalies that have the potential to exacerbate observed long‐term trends. A subgroup of CMIP5 models that realistically simulate both ENSO nonlinearity (diversity) and the AO and AAO‐like patterns are analysed, showing that in the warmer climate, the circulation response in the high‐latitudes to both types of events is amplified in both hemispheres.

A Global Ocean Oxygen Database and Atlas for Assessing and Predicting Deoxygenation and Ocean Health in the Open and Coastal Ocean - Marilaure Grégoire; Véronique Garçon; Hernan Garcia; Denise Breitburg; Kirsten Isensee; Andreas Oschlies; Maciej Telszewski; Alexander Barth; Henry C. Bittig; Jacob Carstensen; Thierry Carval; Fei Chai; et al. (Frontiers in Marine Science, 2021)
In this paper, we outline the need for a coordinated international effort toward the building of an open-access Global Ocean Oxygen Database and ATlas (GO 2 DAT) complying with the FAIR principles (Findable, Accessible, Interoperable, and Reusable). GO 2 DAT will combine data from the coastal and open ocean, as measured by the chemical Winkler titration method or by sensors (e.g., optodes, electrodes) from Eulerian and Lagrangian platforms (e.g., ships, moorings, profiling floats, gliders, ships of opportunities, marine mammals, cabled observatories). GO 2 DAT will further adopt a community-agreed, fully documented metadata format and a consistent quality control (QC) procedure and quality flagging (QF) system. GO 2 DAT will serve to support the development of advanced data analysis and biogeochemical models for improving our mapping, understanding and forecasting capabilities for ocean O 2 changes and deoxygenation trends. It will offer the opportunity to develop quality-controlled data synthesis products with unprecedented spatial (vertical and horizontal) and temporal (sub-seasonal to multi-decadal) resolution. These products will support model assessment, improvement and evaluation as well as the development of climate and ocean health indicators. They will further support the decision-making processes associated with the emerging blue economy, the conservation of marine resources and their associated ecosystem services and the development of management tools required by a diverse community of users (e.g., environmental agencies, aquaculture, and fishing sectors). A better knowledge base of the spatial and temporal variations of marine O 2 will improve our understanding of the ocean O 2 budget, and allow better quantification of the Earth’s carbon and heat budgets. With the ever-increasing need to protect and sustainably manage ocean services, GO 2 DAT will allow scientists to fully harness the increasing volumes of O 2 data already delivered by the expanding global ocean observing system and enable smooth incorporation of much higher quantities of data from autonomous platforms in the open ocean and coastal areas into comprehensive data products in the years to come. This paper aims at engaging the community (e.g., scientists, data managers, policy makers, service users) toward the development of GO 2 DAT within the framework of the UN Global Ocean Oxygen Decade (GOOD) program recently endorsed by IOC-UNESCO. A roadmap toward GO 2 DAT is proposed highlighting the efforts needed (e.g., in terms of human resources).

High-Sustained Concentrations of Organisms at Very low Oxygen Concentration Indicated by Acoustic Profiles in the Oxygen Deficit Region Off Peru - Aurelien Paulmier; Gerard Eldin; José Ochoa; Boris Dewitte; Joël Sudre; Véronique Garçon; Jaques Grelet; Kobi Mosquera-Vásquez; Oscar Vergara; Helmut Maske (Frontiers in Marine Science, 2021)
The oxygen deficient mesopelagic layer (ODL) off Peru has concentrations below 5 μmol O 2 kg –1 and is delimited by a shallow upper oxycline with strong vertical gradient and a more gradual lower oxycline ( lOx ). Some regions show a narrow band of slightly increased oxygen concentrations within the ODL, an intermediate oxygen layer ( iO 2 ). CTD, oxygen and lowered Acoustic Doppler Current Profiler (LADCP, 300 kHz) profiles were taken on the shelf edge and outside down to mostly 2000 m. We evaluate here the acoustic volume backscatter strength of the LADCP signal representing organisms of about 5 mm size. Dominant features of the backscatter profiles were a minimum backscatter strength within the ODL, and just below the lOx a marked backscatter increase reaching a maximum at less than 3.0 μmol O 2 kg –1 . Below this maximum, the acoustic backscatter strength gradually decreased down to 1000 m below the lOx . The backscatter strength also increased at the iO 2 in parallel to the oxygen concentration perturbations marking the iO 2 . These stable backscatter features were independent of the time of day and the organisms represented by the backscatter had to be adapted to live in this microaerobic environment. During daylight, these stable structures were overlapped by migrating backscatter peaks. Outstanding features of the stable backscatter were that at very low oxygen concentrations, the volume backscatter was linearly related to the oxygen concentration, reaching half peak maximum at less than 2.0 μmol O 2 kg –1 below the lOx , and the depth-integrated backscatter of the peak below the lOx was higher than the integral above the Ox. Both features suggest that sufficient organic material produced at the surface reaches to below the ODL to sustain the major fraction of the volume backscatter-producing organisms in the water column. These organisms are adapted to the microaerobic environment so they can position themselves close to the lower oxycline to take advantage of the organic particles sinking out of the ODL.

Environmental Drivers of Mesophotic Echinoderm Assemblages of the Southeastern Pacific Ocean - Ariadna Mecho; Boris Dewitte; Javier Sellanes; Simon van Gennip; Erin E. Easton; Joao B. Gusmao (Frontiers in Marine Science, 2021)
Mesophotic ecosystems (50–400 m depth) of the southeastern Pacific have rarely been studied because of the logistical challenges in sampling across this remote zone. This study assessed how oxygen concentrations and other environmental predictors explain variation in echinoderm assemblages at these mesophotic systems, where this group is among the predominant fauna. We compiled data on echinoderm taxa at 91 sampling stations, from historical and recent surveys (between 1950 and 2019), covering a longitudinal gradient of approximately 3,700 km along with the Nazca, Salas y Gómez, and Juan Fernández ridges. Uni- and multivariate model-based tools were applied to analyze the patterns of benthic fauna in relation to environmental factors. Our results indicate a significant positive relationship between echinoderm species richness and depth, oxygen, and salinity. Changes in echinoderm community composition were significantly explained by oxygen, longitude, and chlorophyll- a . We observed notable species turnovers at ∼101 and ∼86°W, where assemblages tend to be more variable across stations. This turnover possibly reflects the effects of physical barriers to dispersion (e.g., currents) and habitat changes. Echinoderm assemblages observed around Easter and Desventuradas Islands presented a high occurrence of potentially endemic taxa and distinct species assemblages. This study is the first to assess the structure of mesophotic echinoderm assemblages of the southeastern Pacific Ocean along a large spatial scale. The information reported here could help design appropriate management tools for the vast, recently created, marine protected areas in the southeastern Pacific.

Change in strong Eastern Pacific El Niño events dynamics in the warming climate - Aude Carréric; Boris Dewitte; Wenju Cai; Antonietta Capotondi; Ken Takahashi; Sang-Wook Yeh; Guojian Wang; Virginie Guémas (Climate Dynamics, 2020)

Dynamics of the Carbonate System Across the Peruvian Oxygen Minimum Zone - Jose M. Hernandez-Ayon; Aurélien Paulmier; Veronique Garcon; Joel Sudre; Ivonne Montes; Cecilia Chapa-Balcorta; Giovanni Durante; Boris Dewitte; Cristophe Maes; Marine Bretagnon (Frontiers in Marine Science, 2019)

Ocean Climate Observing Requirements in Support of Climate Research and Climate Information - Detlef Stammer; Annalisa Bracco; Krishna AchutaRao; Lisa Beal; Nathaniel L. Bindoff; Pascale Braconnot; Wenju Cai; Dake Chen; Matthew Collins; Gokhan Danabasoglu; Boris Dewitte; Riccardo Farneti; et al. (Frontiers in Marine Science, 2019)

A theoretical model of strong and moderate El Niño regimes - Ken Takahashi; Christina Karamperidou; Boris Dewitte (Climate Dynamics, 2019)

Diversity of moderate El Niño events evolution: role of air–sea interactions in the eastern tropical Pacific - Boris Dewitte; Ken Takahashi (Climate Dynamics, 2019)

Tropical Pacific Observing System - Neville Smith; William S. Kessler; Sophie Cravatte; Janet Sprintall; Susan Wijffels; Meghan F. Cronin; Adrienne Sutton; Yolande L. Serra; Boris Dewitte; Peter G. Strutton; Katherine Hill; Alex Sen Gupta; et al. (Frontiers in Marine Science, 2019)

Decadal modulation of the relationship between intraseasonal tropical variability and ENSO - Daria Gushchina; Boris Dewitte (Climate Dynamics, 2019)

Hydroclimatic change disparity of Peruvian Pacific drainage catchments - Pedro Rau; Luc Bourrel; David Labat; Frédéric Frappart; Denis Ruelland; Waldo Lavado; Boris Dewitte; Oscar Felipe (Theoretical and Applied Climatology, 2018)

Rainfall along the coast of Peru during strong El Niño events - Janeet Sanabria; Luc Bourrel; Boris Dewitte; Frédéric Frappart; Pedro Rau; Olimpio Solis; David Labat (International Journal of Climatology, 2018)
While, climatologically, most areas of the Peruvian Pacific region do not experience precipitation, they can be affected by heavy rain and flooding during strong El Niño events with severe socio‐economic impacts. Only four strong El Niño events took place within the last five decades (1972/1973, 1982/1983, 1997/1998 and 2015/2016) which led to significant rainfall events in the northern part of Peru. Here a detailed analysis of the evolution of precipitation during these events was performed using gauge records from 1964 to 2016 from a network of 145 meteorological stations located along the Peruvian Pacific region. Through empirical orthogonal function analysis, the rainfall anomalies variability is interpreted as resulting from the combination of a meridional see‐saw mode (North–South) (Ep mode) and a zonal see‐saw mode (East–West) (Cp mode) that represent, respectively, 34 and 21% of the explained variance. It is shown that the extreme 1982/1983 and 1997/1998 El Niño events have a dominant projection on the Ep mode that has a strong loading in the northern region, while the 1972/1973 and 2015/2016 El Niño events have a relatively weak projection onto the Ep mode (about ten times less at the peak rainy season than the extreme events) and mostly project onto the Cp mode. Also, it is shown that while all events are associated with positive rainfall anomalies in the northern part of Peru which is accounted for by the Ep mode, the evolution of rainfall anomalies along the Cp mode exhibits a significant dispersion. This suggests that the impact of strong El Niño events on the highlands along the coast cannot solely be inferred from the magnitude of the sea surface temperature anomalies in the central equatorial Pacific. Overall, our study illustrates the nonlinearity of the ENSO teleconnection on the rainfall along the coast of Peru during strong El Niño events.

First Deployment and Validation of in Situ Silicate Electrochemical Sensor in Seawater - Carole Barus; Dancheng Chen Legrand; Nicolas Striebig; Benoit Jugeau; Arnaud David; Maria Valladares; Praxedes Munoz Parra; Marcel E. Ramos; Boris Dewitte; Véronique Garçon (Frontiers in Marine Science, 2018)

Seasonal variability of the Ekman transport and pumping in the upwelling system off central-northern Chile (∼ 30° S) based on a high-resolution atmospheric regional model (WRF) - Luis Bravo; Marcel Ramos; Orlando Astudillo; Boris Dewitte; Katerina Goubanova (Ocean Science, 2016)
Two physical mechanisms can contribute to coastal upwelling in eastern boundary current systems: offshore Ekman transport due to the predominant alongshore wind stress and Ekman pumping due to the cyclonic wind stress curl, mainly caused by the abrupt decrease in wind stress (drop-off) in a cross-shore band of 100 km. This wind drop-off is thought to be an ubiquitous feature in coastal upwelling systems and to regulate the relative contribution of both mechanisms. It has been poorly studied along the central-northern Chile region because of the lack in wind measurements along the shoreline and of the relatively low resolution of the available atmospheric reanalysis. Here, the seasonal variability in Ekman transport, Ekman pumping and their relative contribution to total upwelling along the central-northern Chile region (∼ 30° S) is evaluated from a high-resolution atmospheric model simulation. As a first step, the simulation is validated from satellite observations, which indicates a realistic representation of the spatial and temporal variability of the wind along the coast by the model. The model outputs are then used to document the fine-scale structures in the wind stress and wind curl in relation to the topographic features along the coast (headlands and embayments). Both wind stress and wind curl had a clear seasonal variability with annual and semiannual components. Alongshore wind stress maximum peak occurred in spring, second increase was in fall and minimum in winter. When a threshold of −3 × 10−5 s−1 for the across-shore gradient of alongshore wind was considered to define the region from which the winds decrease toward the coast, the wind drop-off length scale varied between 8 and 45 km. The relative contribution of the coastal divergence and Ekman pumping to the vertical transport along the coast, considering the estimated wind drop-off length, indicated meridional alternation between both mechanisms, modulated by orography and the intricate coastline. Roughly, coastal divergence predominated in areas with low orography and headlands. Ekman pumping was higher in regions with high orography and the presence of embayments along the coast. In the study region, the vertical transport induced by coastal divergence and Ekman pumping represented 60 and 40 % of the total upwelling transport, respectively. The potential role of Ekman pumping on the spatial structure of sea surface temperature is also discussed.

Strong and moderate nonlinear El Niño regimes - Ken Takahashi; Boris Dewitte (Climate Dynamics, 2016)

Reinterpreting the thermocline feedback in the western-central equatorial Pacific and its relationship with the ENSO modulation - Boris Dewitte; Sang-Wook Yeh; Sulian Thual (Climate Dynamics, 2013)

The influences of interannual stratification variability and wind stress forcing on ENSO before and after the 1976 climate shift - Yoon-Kyoung Lee; Sang-Wook Yeh; Boris Dewitte; Byung-Kwon Moon; Jong-Ghap Jhun (Theoretical and Applied Climatology, 2012)

Sensitivity of the Humboldt Current system to global warming: a downscaling experiment of the IPSL-CM4 model - Vincent Echevin; Katerina Goubanova; Ali Belmadani; Boris Dewitte (Climate Dynamics, 2012)

Role of the upper ocean structure in the response of ENSO-like SST variability to global warming - Sang-Wook Yeh; Boris Dewitte; Bo Young Yim; Yign Noh (Climate Dynamics, 2010)

Changes in mixed layer depth under climate change projections in two CGCMs - Sang-Wook Yeh; Bo Young Yim; Yign Noh; Boris Dewitte (Climate Dynamics, 2009)

Source of low frequency modulation of ENSO amplitude in a CGCM - Byung-Kwon Moon; Sang-Wook Yeh; Boris Dewitte; Jong-Ghap Jhun; In-Sik Kang (Climate Dynamics, 2007)

Mechanisms of tropical Pacific interannual-to-decadal variability in the ARPEGE/ORCA global coupled model - Carole Cibot; Eric Maisonnave; Laurent Terray; Boris Dewitte (Climate Dynamics, 2005)